Nuclear receptor ligands induce TREM-1 expression on dendritic cells: analysis of their role in tumors. (4th March 2019) - Fontana, Raffaella; Raccosta, Laura; Rovati, Lucrezia; Steffensen, Knut R.; Paniccia, Aida; Jakobsson, Tomas; Melloni, Giulio; Bandiera, Alessandro; Mangili, Giorgia; Bergamini, Alice; Maggioni, Daniela; Doglioni, Claudio; et al.
ABSTRACT: Dendritic cells (DCs) initiate adaptive immune responses after their migration to secondary lymphoid organs. The LXR ligands/oxysterols and the RXR ligand 9-cis Retinoic Acid (9-cis RA) were shown to dampen DC migration to lymphoid organs through the inhibition of CCR7 expression. We performed transcriptomics of DCs undergoing maturation in the presence of the LXR ligand 22R-Hydroxycholesterol (22R-HC). The analysis highlighted more than 1500 genes modulated by 22R-HC treatment, including the triggering receptor expressed on myeloid cells (TREM)-1, which was found markedly up-regulated. We tested the effect of other nuclear receptor ligands (NRL) and we reported the induction of TREM-1 following RXR, RAR and VDR activation. From a functional point of view, triggering of TREM-1 induced by retinoids increased TNFα and IL-1β release, suggesting an active role of NRL-activated TREM-1 + DCs in inflammation-driven diseases, including cancer. Consistently with this hypothesis we detected DCs expressing TREM-1 in pleural effusions and ascites of cancer patients, an observation validated by the induction of TREM-1, LXR and RAR target genes when monocyte-DCs were activated in the presence of tumor-conditioned fluids. Finally, we observed a better control of LLC tumor growth in Trem-1 −/- bone marrow chimera mice as compared to wild type chimera mice. Future studies will be necessary to shed light on the mechanism of TREM-1 induction by distinct NRL, and to characterize the role of TREM-1 + DCs in tumor growth.